Thermal desorption effects on fragment ion production from multi-photon ionized uridine and selected analogues. Issue 34 (9th June 2021) - Bocková, J.; Rebelo, A.; Ryszka, M.; Pandey, R.; Mészáros, D.; Limão-Vieira, P.; Papp, P.; Mason, N. J.; Townsend, D.; Nixon, K. L.; Vizcaino, V.; Poully, J.-C.; et al.
Abstract : This work reveals the first experimental evidence supporting isomer-dependence in the radiation response of a nucleoside. Abstract : Experiments on neutral gas-phase nucleosides are often complicated by thermal lability. Previous mass spectrometry studies of nucleosides have identified enhanced relative production of nucleobase ions ( e.g. uracil + from uridine) as a function of desorption temperature to be the critical indicator of thermal decomposition. On this basis, the present multi-photon ionization (MPI) experiments demonstrate that laser-based thermal desorption is effective for producing uridine, 5-methyluridine, and 2′-deoxyuridine targets without thermal decomposition. Our experiments also revealed one notable thermal dependence: the relative production of the sugar ion C5 H9 O4 + from intact uridine increased substantially with the desorption laser power and this only occurred at MPI wavelengths below 250 nm (full range studied 222–265 nm). We argue that this effect can only be rationalized plausibly in terms of changing populations of different isomers, tautomers, or conformers in the target as a function of the thermal desorption conditions. Furthermore, the wavelength threshold behavior of this thermally-sensitive MPI channel indicates a critical dependence on neutral excited state dynamics between the absorption of the first and second photons. The experimental results are complemented by density functional theory (DFT) optimizations of the lowest-energy structure of uridine and two further conformers distinguished by different orientations of the hydroxymethyl group on the sugar part of the molecule. The energies of the transitions states between these three conformers are low compared with the energy required for decomposition.